2004
DOI: 10.3201/eid1002.030731
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and Molecular Biologic Methods for SARS-associated Coronavirus Infection, Taiwan

Abstract: Severe acute respiratory syndrome (SARS) has raised a global alert since March 2003. After its causative agent, SARS-associated coronavirus (SARS-CoV), was confirmed, laboratory methods, including virus isolation, reverse transcriptase–polymerase chain reaction (RT-PCR), and serologic methods, have been quickly developed. In this study, we evaluated four serologic tests ( neutralization test, enzyme-linked immunosorbent assay [ELISA], immunofluorescent assay [IFA], and immunochromatographic test [ICT]) for det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(142 citation statements)
references
References 10 publications
7
132
1
2
Order By: Relevance
“…Numerous procedures based on nucleic acid amplification have been reported (84,85). These include RT-PCR and nucleic acid sequencebased amplification (NASBA).…”
Section: Detection Of Virus/viral Rna Although Cells Such As Vero Canmentioning
confidence: 99%
“…Numerous procedures based on nucleic acid amplification have been reported (84,85). These include RT-PCR and nucleic acid sequencebased amplification (NASBA).…”
Section: Detection Of Virus/viral Rna Although Cells Such As Vero Canmentioning
confidence: 99%
“…SARS originated from Southern China and then spread to many countries and regions, including Taiwan [Chan et al, 2004]. The latter experienced a SARS outbreak from March to June of 2003 and suffered from 680 probable cases of SARS with 81 confirmed deaths [Wu et al, 2004]. In our hospital, a 23-year-old patient recovered from SARS and was ready for discharge on the 17th day after the onset of the disease.…”
Section: Introductionmentioning
confidence: 98%
“…Several serological studies with SARS patient sera have been reported and these show varying sensitivities and specificities. 5,6,8 The reference serological method is the neutralisation test and this was compared to enzyme linked immunosorbent assay (ELISA), immunofluorescence assays (IFA) and the immunochromatic test (ICT). Antibody determination using IFA or ELISA was the most reliable method for identifying infections with SARSCoV.…”
Section: Serological Testsmentioning
confidence: 99%